2017
DOI: 10.1080/00224499.2017.1295300
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional Epistemologies of Ignorance: How Behavioral and Social Science Research Shapes What We Know, Think We Know, and Don’t Know About U.S. Black Men’s Sexualities

Abstract: Epistemologies of ignorance describe how ignorance influences the production of knowledge. Advancing an intersectional epistemologies of ignorance approach that examines how conscious (or unconscious) ignorance about racism, heterosexism, and classism shapes empirical knowledge about Black men's sexualities, we conducted a critical review of the behavioral and social science research on U.S. Black men, ages 18 and older, for two time frames: pre-1981 and the most recent decade, 2006-2016. Our search yielded 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 145 publications
2
77
0
Order By: Relevance
“…Individuals with anticipated, perceived, enacted, or internalized HIV stigma often inhabit various marginalized social identities; and have exposure to multiple forms of oppression, known as intersectional stigma. Forms of privilege and oppression intersect with HIV (138,139), and other stigmatized social identities, such as race and ethnicity, nationality, gender identity, sexual orientation, sexual practices, mental health, and addictions that may increase the cumulative burden of psychological distress (140), contribute to poor clinical outcomes (141) and create disparities in HIV screening (141,142), especially among Black men (143,144). However, stigmatized identities have often been analyzed in isolation, ignoring the convergence of intersecting forms of stigma or multiple stigmatized identities that is the reality for many individuals and groups (145).…”
Section: Intersectional Stigmamentioning
confidence: 99%
“…Individuals with anticipated, perceived, enacted, or internalized HIV stigma often inhabit various marginalized social identities; and have exposure to multiple forms of oppression, known as intersectional stigma. Forms of privilege and oppression intersect with HIV (138,139), and other stigmatized social identities, such as race and ethnicity, nationality, gender identity, sexual orientation, sexual practices, mental health, and addictions that may increase the cumulative burden of psychological distress (140), contribute to poor clinical outcomes (141) and create disparities in HIV screening (141,142), especially among Black men (143,144). However, stigmatized identities have often been analyzed in isolation, ignoring the convergence of intersecting forms of stigma or multiple stigmatized identities that is the reality for many individuals and groups (145).…”
Section: Intersectional Stigmamentioning
confidence: 99%
“…Black males face even greater stressors and challenges due to historical trauma, systemic oppression, prejudice and economic disparities rooted in racism (Bowleg, et al, 2017;Harris, 1995;Lipscomb, 2016). Black males are disproportionately over-represented in the United States jails and prisons, and the unemployment rate for Black men is over twice the rate of White men of the same age (Bowleg, et al, 2017).…”
Section: The Realities Of Black Mental Healthmentioning
confidence: 99%
“…Black males face even greater stressors and challenges due to historical trauma, systemic oppression, prejudice and economic disparities rooted in racism (Bowleg, et al, 2017;Harris, 1995;Lipscomb, 2016). Black males are disproportionately over-represented in the United States jails and prisons, and the unemployment rate for Black men is over twice the rate of White men of the same age (Bowleg, et al, 2017). They are disproportionately exposed to poverty, unstable housing, increased HIV risk, homicide, unintentional injuries, suicide, heart disease, and cancer (Bowleg, et al, 2017;Bowleg & Raj, 2012;Centers for Disease Control and Prevention [CDC], 2015;Dunlap, Benoit & Graves, 2013).…”
Section: The Realities Of Black Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical factors have been shown to affect HIV incidence and prevalence rates among Black MSM, such as infrequent HIV/STI testing patterns, undiagnosed and untreated HIV/STI infections, higher frequencies of HIV/STIs within sexual networks, and suboptimal viral load suppression rates [14][15][16][17][18][19][20][21][22]. In addition, a growing body of research has shown that stigma has influenced the increasing disproportionate HIV disease burden among Black MSM (e.g., racism, homophobia, HIV-related stigma and discrimination, and religiosity-based stigma and discrimination) [8,[23][24][25][26][27][28][29][30][31]. Taken together, these studies provide a core basis for understanding key contexts that contribute to the increased HIV vulnerability among Black MSM.…”
Section: Introductionmentioning
confidence: 99%